Insurance, weather, and financial stability - Charles M. Kahn; Ahyan Panjwani; Jo\~ao A. C. Santos (Federal Reserve Bank of New York, 2024)
In this paper, we introduce a model to study the interaction between insurance and banking. We build on the Federal Crop Insurance Act of 1980, which significantly expanded and restructured the decades-old federal crop insurance program and adverse weather shocks - over-exposure of crops to heat and acute weather events - to investigate some insights from our model. Banks increased lending to the agricultural sector in counties with higher insurance coverage after 1980, even when affected by adverse weather shocks. Further, while they increased risky lending, they were sufficiently compensated by insurance such that their overall risk did not increase meaningfully. We discuss the implications of our results in the light of potential changes to insurance availability as a consequence of global warming.
Keywords: Q54; G22; G21; G28; 330; climate risks; insurance; bank lending; financial stability